Quantum Dot-sensitized Solar Cells: A Review - Pooja Bhambhani (Bulletin of Electrical Engineering and Informatics, 2018)
Quantum dot-sensitized solar cell (QDSSC) has an analogous structure and working principle to the dye sensitizer solar cell (DSSC). It has drawn great attention due to its unique features, like multiple exciton generation (MEG), simple fabrication and low cost. The power conversion efficiency (PCE) of QDSSC is lower than that of DSSC. To increase the PCE of QDSSC, it is required to develop new types of working electrodes, sensitizers, counter electrodes and electrolytes. This review highlights recent developments in QDSSCs and their key components, including the photoanode, sensitizer, electrolyte and counter electrode.